FOLIAR MICROMORPHOLOGY OF GASTERIA BICOLOR HAW. (ASPHODELACEAE) FROM SOUTH AFRICA - Otang, Wilfred Mbeng; Grierson, Donald Scott; Ndip, Roland Ndip (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: The succulent genus, Gasteria, which comprises 16 species, is endemic to South Africa and has its main centre of distribution in the Savanna Region of the Eastern Cape. Whereas G. bicolor has been investigated phyto-chemically and pharmacologically, not much data concerning the anatomical and micro-morphological features can be found in literature. Materials and Methods: This study was undertaken, using light and scanning electron microscopy to obtain information on the micro-morphological features of this important medicinal plant to facilitate its identification and authentication. The elemental composition of the leaf was determined by energy dispersive X-ray spectroscopy (EDXS). Results: The epidermal cells are either hexagonal or pentagonal in form, and are compactly arranged with undulate anti-clinal cell walls. The epidermal cell width was approximately 50 μm. Stomata apertures are elliptical and the upper epidermis of the leaf has paracytic stomata which are slightly raised above the epidermal surface with 4 to 5 subsidiary cells surrounding each stoma. Based on the EDXS microanalysis, the mineral crystals present at the level of the mesophyll of G. bicolor were probably mixtures of calcium oxalate, calcium sulphate and silica. Conclusion: The co-occurrence of aluminum suggests the potential role of the crystals in detoxification of aluminum and heavy metals, as reported previously.